Perhitungan Premi Asuransi Pertanian Berbasis Indeks Curah Hujan Pada Komoditas Cabai Merah Menggunakan Metode Black-Scholes - Musfawarman, Eko; rosita, silvia; Arsita, Sari (AKTUARIA, 2024)
Agriculture is a sector that plays an important role in supporting the Indonesian economy. In this sector there is a risk of crop failure caused by unfavorable rainfall. One of the agricultural commodities whose production is influenced by rainfall is red chili. Rainfall index-based agricultural insurance is a solution that can protect red chili farmers from the risk of crop failure where the premium to be paid can be calculated using the Black-Scholes. The purpose of this study was to calculate the premium paid on agricultural insurance based on the rainfall index on red chili commodities using the Black-Scholes method. Assumptions in the Black-Scholes such as not paying dividends, the type of option used is the European type option, there are no transaction costs, risk-free interest, and the operated data meets the assumption of a lognormal distribution to support this research in determining agricultural insurance premiums based on the rainfall index. This study has the result that the amount of premium to be paid when the trigger (rainfall) is 611.13 mm is Rp.434.228.97 and when the trigger is 720.1 mm, the premium to be paid is Rp.1.917.972.34. The increase in rainfall affects the amount of premium that must be paid.